CHALLENGES OF TRANSLATING DIGITAL ECONOMY TERMINOLOGY BETWEEN UZBEK AND ENGLISH LANGUAGES - Nozima Niyozova Ilhom qizi (Web of Journals Publishing, 2026)
The rapid development of the digital economy has led to the emergence of numerous new terms and concepts that require accurate and consistent translation across languages. For languages with different linguistic structures and levels of terminological standardization, such as Uzbek and English, this task presents significant challenges. This article examines the main difficulties encountered in translating digital economy terminology between Uzbek and English. It analyzes linguistic, semantic, morphological, and cultural factors influencing translation quality, including neologisms, loanwords, abbreviations, and conceptual mismatches. The study also explores existing translation strategies and evaluates their effectiveness. Based on the analysis, the article proposes practical recommendations for improving terminological consistency and translation accuracy in the field of the digital economy.
Keywords: Digital economy, terminology translation, Uzbek language, English language, neologisms, loanwords, localization, semantic equivalence, terminological standardization.